2022
DOI: 10.1039/d2tb00379a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heparin-loaded poly(ethylene glycol)-based hydrogels as anti-thrombogenic surface coatings for extracorporeal membrane oxygenation

Abstract: Extracorporeal membrane oxygenation (ECMO), a critical life-sustaining tool, faces significant challenges for the maintenance of normal haemostasis due to the large volume of circulating blood continuously in contact with artificial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…18 Despite these concerns, Carmeda heparin-containing coatings are still considered the ‘gold standard’ for anticoagulant coatings. 14…”
Section: Bioactive Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Despite these concerns, Carmeda heparin-containing coatings are still considered the ‘gold standard’ for anticoagulant coatings. 14…”
Section: Bioactive Coatingsmentioning
confidence: 99%
“…This disrupts the coagulation and anticoagulation systems and leads to an increased risk of bleeding and thrombotic events (BTEs). 8,[12][13][14] Generally, blood thrombosis is more likely to occur inside ECMO circuits than in vivo (Fig. 1), and histological studies have shown that thrombi at different sites have different compositions.…”
Section: Introductionmentioning
confidence: 99%
“…The superior hydrophilicity of PMSEA endowed the modified surface substrate with enhanced antifouling properties as evidenced by a lower level of protein and cell adsorption, compared with the POEGA-modified surface. 146 A further study involved modifying poly(4-methyl-1-pentene) (PMP) film, a base material of the membrane used in extracorporeal membrane oxygenation (ECMO) devices, 278 and validated the excellent antifouling properties of PMSEA. 279 Through the modification with PMSEA brushes by γ-ray irradiation-initiated polymerization, the surface wettability of the PMP film was changed from hydrophobic to hydrophilic, leading to drastically reduced surface adhesion of plasma proteins and platelets.…”
Section: Poly(2-oxazolines) (Pox)mentioning
confidence: 99%
“…Implantable medical devices play a vital and ubiquitous role in modern healthcare, serving essential functions in both diagnostics and therapies. However, fouling due to biological adhesion of microbial or thrombotic agents on medical devices has become a serious issue and can result in various negative consequences, including infection, reduced device performance, and potential treatment failure, as well as complications such as inflammatory and immune responses. , Antifouling polymer brushes have been applied as an innovative approach to address the biofouling of medical devices. By employing antifouling polymer brushes on the surface of medical devices such as catheters, ,,,, stents, ,, and implants, ,,,, the adhesion of biomolecules such as serum or body fluid proteins and further attachment of platelets or bacteria to the surface of medical devices can be greatly diminished, enhancing the biocompatibility, hemocompatibility, and the period of usage of the devices and eventually improving the patient compliance and treatment outcomes.…”
Section: Applications Of Antifouling Surface Polymer Brushesmentioning
confidence: 99%
“…31,34,35 Several reports have been devoted to PVC tubing hemocompatibility improvement through surface grafting or surface coating to prevent thrombosis. 6,[36][37][38][39] However, the sophisticated chemical grafting procedures and harsh preparation conditions significantly limit expansion to large-scale application and may compromise the surface selectivity characteristics of the substrate. 2,31,40 The flushing of blood would easily scour or even delaminate the anticoagulant coating.…”
Section: Introductionmentioning
confidence: 99%